Neuroimaging in Parkinson's disease and related disorders - Politis, Marios; Wilson, Heather C.; De Natale, Edoardo Rosario (Academic Press, an imprint of Elsevier, 2023)
"Neuroimaging in Parkinson's Disease and Related Disorders discusses the advances of molecular, structural and functional neuroimaging techniques associated with the etiology, pathophysiology, effects and complications of novel therapies in Parkinson's and related disorders. With new neuroimaging methodologies emerging over the past five years, this book provides a comprehensive overview of new technologies and research. Sections discuss the biomarker value of neuroimaging of the brain to understand disease progression in vivo in actual patients with Parkinson's disease and related disorders. Readers will be updated on in vivo pathology and pathophysiology in Parkinson's disease and in a number of related disorders. Also discussed is the association between clinical symptoms, clinical progression, and molecular, structural, and functional changes in the brain of patients with Parkinson's disease and related disorders."--